2016
DOI: 10.14202/vetworld.2016.759-765
|View full text |Cite
|
Sign up to set email alerts
|

Testicular pathology, gonadal and epididymal sperm reserves of Yankasa rams infected with experimental Trypanosoma brucei brucei and Trypanosoma evansi

Abstract: Aim:The study was conducted to evaluate the pathological effects of trypanosomosis on the testes, gonadal, and epididymal sperm reserves of Yankasa rams for 98 days.Materials and Methods:A total of 16 Yankasa rams, aged between 24 and 30 months and weighed between 22 and 25 kg, were acclimatized for a period of 2-months in a clean fly proof house and were adequately fed and given water ad-libitum. Of the 16 rams, 12 that were clinically fit for the experiment at the end of the acclimatization period were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
3
5
0
Order By: Relevance
“…In contrast, the rate of dead sperm increased, accompanied by increased abnormalities in morphology. These results were the same as those reported in Yankasa rams infected with T. evansi experimentally [ 5 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, the rate of dead sperm increased, accompanied by increased abnormalities in morphology. These results were the same as those reported in Yankasa rams infected with T. evansi experimentally [ 5 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…The histopathology of the testis from infected camels in the current study showed degenerative changes of the seminiferous tubules characterized by vacuolation with scarce sperm cells and spermatids. The same results were detected in the experiment of rams infected with T. brucei and T. evansi [ 36 ]. Furthermore, another study was carried out in a deer infected with the same parasite, which revealed that the seminiferous tubule has degeneration accompanied by degeneration of sperm in the ducts of the epididymis [ 39 ].…”
Section: Discussionsupporting
confidence: 83%
“…Also, most of the epididymal sperm reserves were empty but contained proteinaceous fluid. Atrophy of the seminiferous tubules has been reported in T. evansi infected camels (20) and sheep infected with T. brucei (19), and T. vivax (35). Atrophy is the result of progressive testicular degeneration (36), which is caused by intermittent fluctuations in temperature and invasion of the testis by the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…T. brucei brucei causes a varying degree of disease associated with the reproductive system among domestic animals. In males, it is characterized by poor quality semen, decreased testosterone level, penile protrusion, preputial inflammation, scrotal dermatitis, loss of libido, increased reaction time, sperm abnormalities, orchitis and severe testicular degeneration (5,16,17,18,19,20). In females, it is manifested by abortion, stillbirths, posterior paresis as well as reproductive and endocrine lesions (21,22,23,24).…”
Section: Introductionmentioning
confidence: 99%
“…During the pathogenesis, degenerative changes in the testes, delayed puberty further leads to loss of libido was reported in trypanosomosis. According to Wada et al (2016) direct trypanosomal damage and pathological changes in the testis are responsible for the aspermia in Trypanosoma evansi infected male goats. During the T. vivax infection it causes testicular and epididymal lesions and leads to development of the infertility and sterility in animals chronically affected with T. vivax (Sekoni et al 2004).…”
Section: Treatment and Discussionmentioning
confidence: 99%